Effectiveness of literature circles in developing english language reading ability: a systematic review - Ma, Lei; Ismail, Lilliati; Saharuddin, Norzihani (Canadian Center of Science and Education, 2023)
English reading ability is essential to overall language proficiency because our learning depends heavily on written materials. As a highly evolved form of collaborative learning originating in the L1 context, literature circles can provide a perfect scaffolding for reading, discussion and sharing. Thus, this reading strategy has also been widely used in L2 learning. This systematic review examines the effectiveness of literature circles in improving English language reading ability. An analysis is conducted in reference to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology. Based on the search keywords, a total of 19 articles related to the benefits of literature circles for English reading comprehension ability are identified from Scopus, Google Scholar, Dimensions and Education Resources Information Center databases. The findings from the synthesis show a trend among literature circles to integrate more modern technology and to adopt more diversified reading materials. The identified themes related to reading ability consist of six areas: self-regulation, reading skills, positive attitude, cultural awareness, critical-thinking skills and reading engagement. It is hoped this systematic review will inspire language instructors to implement literature circles to improve training students' English reading ability.